De don Álvaro de Luna a doña María la Brava: el fin de un ciclo. Issue 1 (2nd January 2019) - Pereira, Montserrat Ribao
Abstract: King Juan II of Castille's court is a common topic in nineteenth-century literature, featured in novels, short stories, plays, and poems alike. When Eduardo Marquina's Doña María la Brava (1909) was previewed in the early years of the twentieth century, critics objected to the blending of the legendary and the historical represented respectively by the characters of María de Monroy and Álvaro de Luna since they evaluated Marquina's play according to nineteenth-century interpretations of the role of the constable Luna. Yet, as this article argues, Doña María la Brava appropriates the characters of King Juan's court (Luna, the poets, and the noblemen) with the new objective of showing the decadence of Castille. Thus, Marquina's play stages Castille's crisis shortly after the political disaster of 98 and the significant historical events of the African war and "The Tragic Week." I claim that this play inaugurates a new form of reading the fifteenth century which strongly differs from previous readings and necessarily means the end of the nineteenth-century literary cycle of King Juan II.